Symptoms and side effects in chronic non‐cancer pain patients: clinical implications and development of new assessment tools. Issue 8 (29th May 2015) - Olsen, T. S.; Jonsson, T.; Højsted, J.; Sjøgren, P.; Christrup, L.
<x xml:space="preserve">Abstract</x> Objective To improve a 41‐item screening tool evaluated in our previous study by making it more simple and convenient to patients and at the same time maintain the level of information and the sensitivity. Methods In a prospective, two‐period questionnaire study, patients suffering from chronic pain of non‐cancer origin for more than 6 months, were asked to fill in two questionnaires: QSSE‐41 or QSSE‐33 and SF‐36. The first part of the study (QSSE‐41) included an age‐ and sex‐matched control group. Results A total of 67 patients were included in QSSE‐41 and 60 patients in QSSE‐33. In QSSE‐41, the mean number of symptoms reported by the patient group (12.3) was significantly higher than those reported by the controls (6.8) (P < 0.001). Out of the total number of symptoms, 40.3% were reported to be side effects caused by analgesics, and out of those 61.3% were reported as acceptable and 38.7% as unacceptable side effects. In the QSSE‐33, the mean number of symptoms reported by the patient group was 13.6. Out of the total number of symptoms, 46.3% were reported to be side effects caused by analgesics, and out of those 56.4% were reported as acceptable and 43.6% as unacceptable side effects. Conclusions This new and shorter screening tool QSSE‐33 may substitute the original QSSE‐41 and in clinical use, contribute substantially to a more comprehensive and detailed understanding of symptoms/side effects and may consequently lead to improved therapies.